THE MEDIATING ROLE OF CUSTOMER SATISFACTION IN THE EFFECT OF EXPERIENTIAL MARKETING ON REUSE INTENTION (A STUDY ON D-BANK PRO APPLICATION USERS IN DENPASAR CITY) - Kadek Yudistira Prawirananda; Putu Yudi Setiawan (Adisam Publisher, 2025)
This study aims to examine the effect of experiential marketing on reuse intention by incorporating customer satisfaction as a mediating variable among users of the D-Bank Pro application in Denpasar City. The population consists of users who have been using the application for at least one year, with a total sample size of 130 respondents selected through purposive sampling. Data collection was conducted via surveys using structured questionnaires. The study employed both descriptive and inferential statistical analyses using the Partial Least Squares Structural Equation Modeling (PLS-SEM) method. The results revealed that experiential marketing has a positive and significant effect on both customer satisfaction and reuse intention. Furthermore, customer satisfaction significantly affects reuse intention. The findings also indicate that customer satisfaction partially mediates the effect of experiential marketing on reuse intention.